Réponses

2013-05-15T21:32:59+02:00

a)

E = (3x + 2)² - (3x + 2) (x + 7)

        = (3x + 2) (3x +2) - (3x + 2) (x + 7)

        = (3x * 3x + 3x * 2 + 2 * 3x + 2 * 2) - (3x * x + 3x * 7 + 2 * x + 2 * 7)

        = (9x² + 6x + 6x + 4) - (3x² + 21x + 2x + 14)

        = 9x² + 12x + 4 - 3x² - 21x - 2x - 14

        = 6x² - 11x - 10.

 

b)

E = (3x + 2)²- (3x + 2) (x + 7)

    = (3x + 2) (3x + 2) - (3x + 2) (x + 7)

    = (3x + 2) [(3x + 2) - (x+7)]

    = (3x + 2) (3x + 2 -x -7)

    = (3x + 2) (2x -5)

 

c) Si x = 1

              2

 

E= 6 x 1 - 11 x 1 - 10

           2          2

 

  = 6 - 11 - 10

     2    2

 

  = 5 - 10

     2

 

  = 5 - 10

     2    1

 

   = 5 - 20

      2    2

 

  = -15

       2

  

  = -7,5.

 

 

 

Voilàà.

 

2013-05-15T21:35:44+02:00

E=(3x+2)²-(3x+2)*(x+7)

   3x-3x*x+2+2+2+7

  x+13

 

si tu commpend pas va sur le site maths videos 4éme ou 3éme